De la información rendida y de lo expuesto por facultativos… Testimonios legos y medidas probatorias en el entendimiento judicial de la locura. El caso de Pablo Bartels. Valparaíso, Chile, 1869 - María José Correa Gómez (Centre de Recherches sur les Mondes Américains, 2012)
This presentation focuses on certain procedural aspects of the incapacitation of mentally ill individuals, particularly on the probative value of new judicial ‘evidence’ in the context of the development of medical discipline and the extension of the judicial administration during the second half of the nineteenth century. It explores Pablo Bartel’s interdiction court case, elaborated in 1869, and focuses particularly in legal and expert aspects of the judicial identification of mental incapacity and its interpretation in pathological terms